Validity and reliability test of NIHSS-SDKI and CNS-SDKI in determining actual nursing diagnosis and severity of stroke patients - Fitriana, Erlis Eka; Haryanto, Haryanto; Supriyadi, Supriyadi (Universitas Muhammadiyah Purwokerto, 2024)
Background: The National Institutes of Health Stroke Scale (NIHSS) and The Canadian Neurological Stroke Scale (CNS) are two assessment tools often used for the assessment of neurological status in stroke patients. However, there are no assessment tools that use the standard nursing diagnoses developed in Indonesia, namely the Standar Diagnosis Keperawatan Indonesia (SDKI), developed by the Indonesian National Nurses Association organization.Objective: This study aims to test the validity and reliability of the NIHSS and CNS combined with the SDKI so that they can be used to ensure the accuracy of the measuring instrument, determine its consistency, improve the quality of the assessment, and provide a basis for further research.Methods: This study is an observational study with a cross-sectional study design. The study was conducted at hospitals in Pontianak City, namely Tanjungpura University and Sultan Syarif Mohammad Alkadrie Hospital. The population in this study were all non-hemorrhagic stroke patients treated in the hospital, with a sample size of 30 patients. Sampling in this study was conducted using purposive sampling. Data collection began with the preparation of NIHSS and CNS instruments combined with SDKI, and then respondents' demographic data were collected. Data were analyzed using Pearson Correlation with SPSS statistical tools.Results: Based on the results of the validity and reliability tests, it was found that the NIHSS-SDKI and CNS-SDKI had a calculated r value> from the r table and Cronbach alpha value> 0.7 so that the NIHSS and CNS instruments were declared valid and reliable.Conclusion: Research on the NIHSS-SDKI and CNS-SDKI is valid and reliable, and it can be used as a tool to measure severity and help nurses make nursing diagnoses in accordance with the Indonesian Nursing Diagnosis Standards.